STUDY THE THEORY OF WELFARE STATE IN WEST AND ISLAM IC PERSPECTIVE - djauhari djauhari (Jurnal Pembaharuan Hukum, 2018)
Entering the 20 th century is the era of the Welfare State. In development between countries with one another turns out different from each other. It can thus happen, because it is influenced by the basic philosophy and community life of each country. At least it can be influenced by the basic philosophy of the capitalist, socialist and Islam. Even in the West is now the Welfare State has shifted its meaning to 'Workfare'. In the Welfare State in which the state is responsible for the well-being for its citizens, then the Workfare, now the responsibility of turning on each individual. Each person will be responsible for addressing the problems faced alone / 'individual empowerment'